Syrphine hoverflies are effective pollinators of commercial strawberry - Dylan Hodgkiss; Mark J.F. Brown; Michelle T. Fountain (Journal of Pollination Ecology, 2018)
Recent declines in wild pollinators represent a significant threat to the sustained provision of pollination services. Insect pollinators are responsible for an estimated 45% of strawberry crop yields, which equates to a market value of approximately £99 million per year in the UK alone. As an aggregate flower with unconcealed nectaries, strawberries are attractive to a diverse array of flower-visiting insects. Syrphine hoverflies, which offer the added benefit of consuming aphids during their predatory larval stage, represent one such group of flower visitor, but the extent to which aphidophagous hoverflies are capable of pollinating strawberry flowers remains largely untested. In replicated cage experiments we tested the effectiveness of strawberry pollination by the aphidophagous hoverflies Episyrphus balteatus and Eupeodes latifasciatus, and a mix of four hoverfly taxa, when compared to hand pollination and insect pollinator exclusion. Hoverflies were released into cages, and the strawberry fruits that resulted from pollinated flowers were assessed for quality measures. Hoverfly visitation increased strawberry yields by over 70% and doubled the proportion of marketable fruit, highlighting the importance of hoverflies for strawberry pollination.  A comparison between two hoverfly species showed that Eupeodes latifasciatus visits to flowers produced marketable fruit at nearly double the rate of Episyrphus balteatus, demonstrating that species may differ in their pollination efficacy even within a subfamily. Thus, this study offers compelling evidence that aphidophagous syrphine hoverflies are effective pollinators of commercial strawberry and, as such, may be capable of providing growers with the dual benefit of pollination and aphid control.